Формування системи управління людськими ресурсами міжнародної компанії - Матросов, Олександр Дмитрович; Доуртмес, Пилип Олександрович (НТУ "ХПІ", 2016)
Досліджено стан формування систем управління людськими ресурсами в міжнародному науково-технічному співробітництві. Запропоновані сучасні підходи до формування системи управління людськими ресурсами в Україні. Запропонована система управління людськими ресурсами включає наступні підсистеми: аналіз, планування і прогнозування персоналу; підбір, відбір, розстановка, оцінка і розвиток персоналу; мотивація і оплата праці; раціональне використання персоналу.

The state of human resources system’s forming into international scientific and technical cooperation is examined. The modern approaches to human resources system’s forming in Ukraine are proposed. The proposed system of human resources management includes the following subsystems: analysis, planning of personnel; selecting, estimation and development of personnel; motivation and labour payment; rational using of personnel. The certain volume of activities is proposed according to each subsystem. Special attention is paid to the subsystem of motivation and labour payment as it’s important for stimulation of personnel.
Formation of human resources management system of the international company
Keywords: міжнародне науково-технічне співробітництво; мотиваційні системи; системи розвитку персоналу; раціональне використання персоналу; technical cooperation; motivation systems